On ?- Statistical Convergence - Aral, Nazlim Deniz; Kandemir, Hacer Sengul; Et, Mikail (Amer Inst Physics, 2021)
In in this study, by using definition of rho-statistical convergence which was defined by Cakalli[2], we give some inclusion relations between the set of rho-statistical convergence and strong (S, [rho]) summability.
4th International Conference of Mathematical Sciences (ICMS) -- JUN 17-21, 2020 -- Maltepe Univ, ELECTR NETWORK
Keywords: Statistical convergence; Cesaro summability; Strongly p-Cesaro summability